The Centrality of race to inequality across the world-system - Boatcă, Manuela (2017)
Abstract: While I agree, and have previously argued myself that closer attention should be paid to semiperipheries in terms of their transformative potential, I consider the claim that nonwestern semiperipheries exacerbate and even cause racial/ethnic inequality misleading. In the following, I thus want to caution against what I think are three weak links in the authors’ argument: mistaking visibility for causation, conflating the concept of race with the reality of racism (and its many historical and geopolitical configurations), as well as throwing the baby (white supremacy) out with the bathwater (Western knowledge).I will limit my comments to two aspects. The first one is methodological and concerns the unclear unit of analysis that underlies the authors’ claim for the centrality of non-Western semiperipheries to ethnic/racial inequality. The second aspect is more substantive and targets the relationship between racism and the emergence, functioning, and reproduction of the modern/colonial world system